Impact of influenza virus infection on lung microbiome in adults with severe pneumonia - Yiguo Zhou; Juan Du; Jing-Qin Wu; Quan-Rong Zhu; Ming-Zhu Xie; Lin-Yi Chen; Ya-Qiong Liu; Wei Li; Ting-Fa Zhou; Qing-Bin Lu (BMC, 2023)
Abstract Background Bacterial and viral infections are commonly implicated in the development of pneumonia. We aimed to compare the diversity and composition of lung bacteria among severe pneumonia patients who were influenza virus positive (IFVP) and influenza virus negative (IFVN). Methods Bronchoalveolar lavage fluid specimens were procured from patients diagnosed with severe pneumonia to investigate the microbiome utilizing 16S-rDNA sequencing. The alpha diversity of the microbiome was evaluated employing Chao1, Shannon, and Simpson indexes, while the beta diversity was assessed using principal component analysis and principal coordinate analysis. Linear discriminant analysis effect size (LEfSe) was employed to determine the taxonomic differences between the IFVP and IFVN groups. Results A total of 84 patients with 42 in the IFVP group and 42 in the IFVN group were enrolled. Slightly higher indexes of Shannon and Simpson were observed in the IFVP group without statistically significant difference. The dominant bacterial genera were Streptococcus, Klebsiella, Escherichia-Shigella in the IFVN group and Acinetobacter, Streptococcus, Staphylococcus in the IFVP group. Streptococcus pneumoniae and Acinetobacter baumannii were the most abundant species in the IFVN and IFVP groups, respectively. LEfSe analysis indicated a greater abundance of Klebsiella in the IFVN group. Conclusions Individuals with severe pneumonia infected with IFV exhibit heightened susceptibility to certain bacteria, especially Acinetobacter baumannii, and the underlying mechanism of the interaction between IFV and Acinetobacter baumannii in the progression of pneumonia needs further investigation.